2015
DOI: 10.1039/c5ra15658k
|View full text |Cite
|
Sign up to set email alerts
|

New insights into electrolyte-component biased and transfer- and transport-limited charge recombination in dye-sensitized solar cells

Abstract: We carried out time-resolved charge extraction (TRCE) study on the charge recombination dynamics of open-circuit dye-sensitized solar cells (DSSCs) by examining the temporal evolution of electron density with varying the concentration of electrolyte component tert-butylpyridine (TBP).The charge recombination dynamics extracted from TRCE results exhibit distinctly different temporal behavior depending on the photovoltage or electron density. We proposed a theoretical model of electron density dependent charge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Figure 1s hows the ideal multiple-trapping assistedc harge recombination;h owever,m odificationsa re often required when describing real experiments. [36] If we add k ss in Equation (14), the modified k r -V ph relation is written as: [35] The reasonisascribed to the alternative recombination pathway at low voltage (i.e., the isoenergetic electrons transfer from surfacestate of the TiO 2 to the electrolyte acceptors), which cannot be described by multiple-trapping mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1s hows the ideal multiple-trapping assistedc harge recombination;h owever,m odificationsa re often required when describing real experiments. [36] If we add k ss in Equation (14), the modified k r -V ph relation is written as: [35] The reasonisascribed to the alternative recombination pathway at low voltage (i.e., the isoenergetic electrons transfer from surfacestate of the TiO 2 to the electrolyte acceptors), which cannot be described by multiple-trapping mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…[34] Very recently,w er eported that surface-state-dominated charge recombination obeys the transfer-limited recombination process, which leads to as tationary rate constant k ss . [36] If we add k ss in Equation (14), the modified k r -V ph relation is written as:…”
Section: Resultsmentioning
confidence: 99%
“…The surface traps are localized electronic states in the band gap and are physically located either at the TiO 2 surface or within a tunneling distance from the surface. 16 As the electrons trapped by surface states are intensely localized, the electron transfer from TiO 2 to electrolyte is slower, i.e., the recombination channel is faster. 20 A deeper DOS distribution indicates that more electrons are in deep trap states; thus, the electronic recombination rate of the large working area DSSC (T-2) is faster than that of the small working area cell (T-1).…”
Section: Charge Recombination and Collection As Revealed By Tpv And Tpcmentioning
confidence: 99%
“…This result highlights the importance of improving charge collection efficiency to achieve high-efficiency DSSCs with a large area. This improvement can be achieved by modifying the photoanode morphology, 15 electrolyte engineering, 16 as well as other approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[54,55] In recent years, we have reported that time-resolved charge extraction (TRCE) could act as another effective candidate to study quantitatively the DOS distribution in dye-sensitized solar cells, quantum-dot-sensitized solar cells, and perovskite solar cells. [56][57][58][59][60] However,asignificant limitation of these methods is that the tested system should be connected to as hort or open circuit,s ot hey are unable to investigate the trap states in intrinsic perovskite films without selected electrodes. In contrast, transient infrareda bsorption spectroscopy can be used to measure the DOS distribution of thin films, but it is not easy to identify the characteristic optical signals and the requirement of instrumentsa nd technology is relatively high.…”
Section: Introductionmentioning
confidence: 99%